Common Fiscal Capacity Is Needed to Strengthen Risk Sharing - Antonia Díaz (Intereconomics, 2020)
This asymmetric effect of the shock on economic activities becomes an asymmetric impact on countries depending on their sectoral composition.
Keywords: 330